PERAN APARAT KEPOLISIAN DALAM PENANGGULANGAN TINDAK PIDANA TERORISME DI KABUPATEN POSO - Mohammad Didi Permana; Abdul Manan (Fakultas Hukum Universitas Muhammadiyah Palu, 2020)
Terrorism Criminal Acts in the Region Poso Regency, Second Scope of Research, this research was conducted in Poso Regency, Third Research Methods, Empirical research methods which means the type of legal research that functions to see the law in reality, Fourth Summary of Results, various efforts have been made by the Central Sulawesi Regional Police in tackling terrorism criminal acts include, First, the approach to the community, Second, through law enforcement and the existence of obstacles in the effort to eradicate terrorism, among others, namely the difficulty of the terrain, the factor of the wrong understanding and the lack of police personnel in Poso district. The fifth conclusion is that the police are the frontline in eradicating criminal acts of terrorism. Various efforts have been made by the police in limiting criminal acts of terrorism, including carrying out repressive measures, but criminal acts of terrorism still continue to occur in the Poso Regency. Keywords: Terrorism. Police